1071 SUFE and the Internet: Are Healthcare Information Websites Accessible to Parents?. (12th October 2021) - Mc Carthy, A; Taylor, C
Abstract: Background: Slipped upper femoral epiphysis(SUFE) is an adolescent hip disorder requiring rapid surgical intervention. Faced with the prospect of their child undergoing surgery, many fearful parents will turn to the internet to provide information and reassurance. Previous studies have shown the orthopaedic information can be difficult to comprehend. Objective: Assess the readability of healthcare websites regarding SUFE. Method: The term Slipped Upper Femoral Epiphysis was searched in Google, Bing and Yahoo and evaluated using readability software with seven specialised readability tests. A Flesich Read Ease Score (FRES) score above 65 and a Reading Grade Level (RGL) of sixth grade and under was considered acceptable. Results: 21 unique websites were assessed. The average FRES was 52.5 +/- 15.4. Only 3 websites scored 65 or higher (14%). There was a statistically significant difference between website scores based on affiliation, with physician websites having the overall highest mean(P = 0.004). The average RGL was 8.67 +/- 1.8. Only two websites met the accepted RGL criteria (9.5%) while five websites were marked as extremely difficult to understand (23.8%). Only five websites offered translations (23.8%). There was no statistically significant difference in readability scores between websites which offered translation and those which did not. One-way t-tests showed that both the RGL (p < 0.001; CI: 1.83-3.49) and the FRES (P < 0.001, CI: -19.4 to -5.4) scores were significantly different from the accepted standard. Conclusions: Most websites reviewed were deemed inaccessible. Improving readability would enhance the internet's usability as a healthcare tool for parents.